Feedback Amplification of Neutrophil Function. Issue 6 (June 2016) - Németh, Tamás; Mócsai, Attila
Abstract : As the first line of innate immune defense, neutrophils need to mount a rapid and robust antimicrobial response. Recent studies implicate various positive feedback amplification processes in achieving that goal. Feedback amplification ensures effective migration of neutrophils in shallow chemotactic gradients, multiple waves of neutrophil recruitment to the site of inflammation, and the augmentation of various effector functions of the cells. We review here such positive feedback loops including intracellular and autocrine processes, paracrine effects mediated by lipid (LTB4 ), chemokine, and cytokine mediators, and bidirectional interactions with the complement system and with other immune and non-immune cells. These amplification mechanisms are not only involved in antimicrobial immunity but also contribute to neutrophil-mediated tissue damage under pathological conditions. Trends: Neutrophil recruitment and activation is amplified by positive feedback loops involving neutrophil-derived mediators acting on neutrophils themselves. Feedback amplification is critical for neutrophil-dependent antimicrobial functions but also for neutrophil-mediated tissue damage. Feedback amplification can be observed at various levels including intracellular, autocrine, paracrine, and complex processes. Feedback amplification is involved in various neutrophil functions including cellular polarization, neutrophil recruitment, effector responses, and interactions with other cells. Neutrophil-derived proinflammatory mediators include LTB4, chemokines (primarily CXCL molecules), and various cytokines. Tyrosine kinase signaling pathways play a critical role in feedback amplification of neutrophil function.